1989
DOI: 10.1007/bf00687258
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of oligodendrocyte infection and degeneration in canine distemper encephalomyelitis

Abstract: Canine distemper encephalomyelitis is an important neurological disease of the dog and is also of comparative medical interest. With some viral strains, demyelinating encephalomyelitis is seen; whether or not oligodendrocyte infection occurs has remained controversial. By examining very early white matter lesions unequivocal oligodendrocyte infection has been identified. Accordingly the direct effect of virus on oligodendrocyte viability must be weighed in considering the pathogenesis of this canine CNS infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…The morphological changes are preceded by metabolic dysfunction of these cells, because the activity of cerbroside sulpho-transferase (an oligodendrocyte specific enzyme) decreased markedly soon after infection (Glaus et al, 1990). Following these in vitro observations (Zurbriggen et al, 1987) similar changes of oligodendrocytes were also described in the demyelinating lesions in vivo (Blakemore et al, 1989;Summers and Appel, 1987). There is little doubt that degeneration of these cells lies at the base of the demyelinating process but its mechanism is not yet understood.…”
Section: Degeneration Of Oligodendrocytesmentioning
confidence: 86%
See 1 more Smart Citation
“…The morphological changes are preceded by metabolic dysfunction of these cells, because the activity of cerbroside sulpho-transferase (an oligodendrocyte specific enzyme) decreased markedly soon after infection (Glaus et al, 1990). Following these in vitro observations (Zurbriggen et al, 1987) similar changes of oligodendrocytes were also described in the demyelinating lesions in vivo (Blakemore et al, 1989;Summers and Appel, 1987). There is little doubt that degeneration of these cells lies at the base of the demyelinating process but its mechanism is not yet understood.…”
Section: Degeneration Of Oligodendrocytesmentioning
confidence: 86%
“…Reliable techniques to demonstrate canine oligodendrocytes in histological sections are not yet available, but at the light microscopic level, it has been shown that the majority of infected cells are astrocytes (Mutinelli et al, 1989). Most electron microscopical studies agree that oligodendroglial infection is very rare in distemper (Raine, 1976;Wisniewski et al, 1972;Summers and Appel, 1987;Higgins et al, 1982;Blakemore et al, 1989). However, because of the limited number of cells that can be examined, ultrastructural techniques remain anecdotal.…”
Section: Infection Of the Glial Cells Of The White Mattermentioning
confidence: 99%
“…Most electron microscopy studies agree that infection of oligodendrocytes is very rare in canine distemper [75, 85, 86]. In spite of that, mRNA from CDV can be detected in approximately 8% of the oligodendrocytes around lesions.…”
Section: Mechanisms Of Development Of Neurological Lesionsmentioning
confidence: 92%
“…If MS is caused by a virus triggering a disease with prolonged incubation period, that is some sort of SSPE or combination of ADEM and SSPE, the interesting thought arises whether a virus causing MS should not possibly be sought in healthy persons years prior to the clinical manifestations of the disease in order to equivocally recover the causative factor of the disease. However, when looking for analogies between the neuropathology induced by viral infections of known origin and MS-neuropathology, it seems likely that viral 'signatures' can be found, based on similarities between both, which can provide more clues about the identity of a causative or triggering agent in MS. CDV raises another interesting question: virus can be demonstrated but is mostly present in the 'wrong' cells, that is astrocytes [10,125,[129][130][131][132][133]. Whereas one would suspect a primary infection of oligodendrocytes when finding demyelination, only a small subpopulation of oligodendrocytes is infected in CDE.…”
Section: Final Remarksmentioning
confidence: 99%
“…Therefore a large number of studies have focused on demonstrating the presence of distemper virions in oligodendrocytes. However, at the light microscope level it has been shown that the main white matter cells infected are astrocytes [129] and most studies now agree that oligodendrocyte infection is in fact extremely rare in distemper [125,[130][131][132][133].…”
Section: Acute Phasementioning
confidence: 99%